STUDIES ON THE BIOLOGY OF NEMATOPALAEMON TENUIPES (HENDERSON) IN BOMBAY COAST - Kunju, M M (Indian Journal of Fisheries, 2011)
One of the most conspicuous features of the "dol" net fishery along the Maharashtra coast is the enormous abundance of the small marine palaemonid, Nematopalaemon tenuipes. The only other maritime state where the species supports a commercial fishery is Gujarat (Banerji 1966). It is largely a marine species capable of penetrating estuarine areas, from where it is often commercially exploited, as in the case of the Godavary estuary (Ganapati and Subrahmanyam 1966) and the Sunderbans (Kunju 1956, Rajyalakshmi 1966). The species was formerly known as Leander tenuipes vide Holthuis 1950 for synonymy and Kemp 1917 for identification keys of the different species of the genus